Asthma and rhinitis have different genetic profiles for IL13 , IL17A and GSTP1 polymorphisms - E.P. Resende (Revista Portuguesa de Pneumología, 2017)
Background: Asthma and rhinitis have a complex etiology, depending on multiple genetic and environmental risk factors. An increasing number of susceptibility genes are currently being identied, but the majority of reported associations have not been consistently replicated across populations of different genetic backgrounds. Purpose: To evaluate whether polymorphisms of IL4R (rs1805015), IL13 (rs20541), IL17A (rs2275913) and GSTP1 (rs1695) genes are associated with rhinitis and/or asthma in adults of Portuguese ancestry. Methods: 192 unrelated healthy individuals and 232 patients, 83 with rhinitis and 149 with asthma, were studied. All polymorphisms were detected by real time polymerase chain reaction (PCR) using TaqMan assays. Results: Comparing to controls, signicant association with asthma was observed for GSTP1 rs1695 AA genotype (odds ratio (OR) --- 1.96; 95% CI --- 1.18 to 3.25; p = 0.010). The association sustains for allergic asthma (OR --- 2.17; 95% CI --- 1.23 to 3.80; p = 0.007). IL13 rs20541 GG genotype was associated with less susceptibility to asthma (OR --- 0.55, 95% CI --- 0.33 to 0.94, p = 0.028). Among patients, IL17A rs2275913 AA genotype was less associated with asthma than with rhinitis (OR --- 0.20; 95% CI of 0.07 to 0.56; p = 0.002). A similar association was found for IL13 rs20541 GG genotype (OR --- 0.48; 95% CI of 0.25 to 0.93; p = 0.031). There were no signicant differences in the distribution of allelic and genotypic frequencies between patients and controls for the IL4R polymorphism’ analyzed.